Weight and diet concerns in Finnish female and male athletes - Fogelholm, M.; Hiilloskorpi, H. (Medicine & Science in Sports & Exercise, 1999)
Factors related to eating disorders were studied in five groups of female (N = 173) and male (N = 190) athletes, and in female (N = 79) and male (N = 61) controls. Factors associated with menstrual status were also examined. Result: the risk for eating disorders is dependent on the type of sport. The claim that some female athlete groups are at greater risk than controls did not receive evidence.